Long-term finance provision: National development banks vs commercial banks - Hu, Bo (2022)
Despite its practical significance in promoting long-term economic growth, long-term finance is often in short supply, especially in developing countries. Governments in both developed and developing countries have established national development banks (NDBs) to provide much-needed long-term loans. We have built the first database on NDBs worldwide to systematically examine whether NDBs lend longer than commercial banks in deciding the maturity of their loans. We find that long-term loans constitute a larger proportion of the total loan portfolio in NDBs than that in commercial banks in general and privately owned commercial banks in particular. This result is statistically significant after controlling for country- and bank-level factors. Our study contributes to the literature on loan maturity because we are the first to use a comprehensive panel data to systematically examine whether NDBs—an understudied but important financial intermediary—play a maturity-lengthening role in filling the financing gap.